Design and development of the trailers optimal allocation and schedule model in the supply chain system with considering cross dock with stochastic planning (Nexo Revista Científica, 2021)
Todays, transportation, and logistics engineering processes are among the important issues of organizations in the competitive market. Considering the logistical structure of the logistics engineering and the more attention paid to the logistical tools and, in particular, such as the use of these tools, such as containers (pallets, containers, etc.), transportation equipment (trailer, forklift trucks, etc.), and The art of building the supply and distribution network concerning the main warehouses, cross-dock, and temporary storage, is one of the most critical and contemplative cases. In fact, all these tools work together to maximize system efficiency in the field of logistics concerning the leading impact indicators, including the time of shipment (loading, disloading, the allocation of trailers, etc.). This paper's main goal is to present and develop a mathematical model of trailer schedule planning in possible conditions in the cross-dock. In fact, the main function of this mathematical model is to minimize the total time of the logistics process from the stage of emptying the pallets from the materials producers in the cross docks and assigning the trailer to the door, and finally reloading the pallets to be distributed to the production sites. To solve this model and to analyze the outputs, mixed integer programming was used by GAMS software.